ANALYSIS THAT INFLUENCE BUSINESS PRODUCT DEVELOPMENT THROUGH PERFORMANCE FACTORS IN SMEs. - Suparjo, Suparjo (International Journal of Business, Economics, and Social Development, 2023)
This research aims to determine how the competence of the human resources of small and medium entrepreneurs in Surabaya, Sidaorjo, and how their competencies affect their business performance partially or simultaneously. The research method used is descriptive exploratory. And competency variables are translated into four indicators: Knowledge, Skills, Ability, and Leadership. To answer research problems and test hypotheses, researchers used statistical analysis with SPSS software, especially correlation analysis, regression, F test, and t-test. Purposive sampling was utilized to choose the sample of respondents for this study, who were MSME respondents for leather items from Small and Medium Enterprises in Surabaya, Sidoarjo. The test results demonstrate that by enhancing the performance of MSME employees through leadership elements and their abilities, product creation may be made better.